Low pH Water Impairs the Tactile Sense of the Postlarvae of the Giant Freshwater Prawn Macrobrachium rosenbergii - Gunzo Kawamura; Teodora Bagarinao; Annita Seok Kian Yong; Siti Narasidah; Leong-Sen Lim (Tropical Life Sciences Research, 2018)
The effect of low pH on the tactile sense of Macrobrachium rosenbergii postlarvae was determined in the laboratory by means of two behavioural assays: shelter (netting) occupancy and jumping response to touch stimuli (taps) by a glass micropipette. The postlarvae were acclimated to pH 4, pH 5, pH 6 and pH 7.5 (control) in 45 L aquaria 5?7 d before the experiments. Shelter occupancy decreased with pH and was significantly lower at pH 4 and pH 5 than at pH 6 and in the control. The jumping response instantly followed a tap 93?98% of the time in the control, pH 6 and pH 5 treatments. However, the postlarvae showed significantly lower jumping response (65%) at pH 4, indicating an impaired tactile sense. Low pH 4?5 probably degrades the chitin of the sensory setae and inhibits the surface mechanoreceptors of the prawn postlarvae. Kesan pH rendah terhadap deria sentuhan pasca larva Macrobrachium rosenbergii telah ditentukan dalam makmal melalui dua ujian tingkah laku: penghunian pada substrat (jala) dan respon melompat terhadap sentuhan oleh mikropipet kaca. Pasca larva telah diaklimitasi kepada pH 4, pH 5, pH 6 dan pH 7.5 (kawalan) dalam akuaria 45 L selama 5–7 hari sebelum eksperimen. Bilangan pasca larva yang menghuni pada substrat berkurangan bersama pH dan adalah lebih rendah secara ketara pada pH 4 dan pH 5 berbanding pH 6 dan kawalan. Respon melompat yang segera terhadap 93–98% daripada jumlah sentuhan telah diperhatikan pada pasca larva dalam kumpulan kawalan, pH 6 and pH 5. Namun, pasca larva dalam kumpulan pH 4 menunjukkan jumlah bilangan respon melompat yang lebih rendah secara ketara (65%), menunjukkan penjejasan dalam deria sentuhan mereka. pH yang rendah (dalam pH 4–pH 5) mungkin menjejaskan kitin dalam seta deria dan menghalang permukaan reseptor mekanikal pasca larva udang.